Coercion purified by endorsement transferring ownership of commercial papers in Iraqi law - Dana Hama Baqi Abdul Qader; Baho Parvizkhan Al-Dalawi (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
This research deals with the Principle of Holder in Due Course in negotiable instruments and the nature of the defences which can be avoided by endorsement. It illustrates and discusses the attitude of Iraqi jurisprudence and judicature regarding the principle. It addresses the issues related to the scope of the principle on the defences arising from duress in order to explain the right position of these defences within the principle and their legal bases in the aim of facilitating the correct application of the principle in practice as it is one of the most important principle in the practice of negotiable instruments.